Incidence, Etiology, and Outcomes of Community-Acquired Acute kidney injury in Pediatric Admissions in Malawi. Issue 6 (November 2018) - Evans, Rhys D.R.; Docherty, Marie; Seeley, Anna; Craik, Alison; Mpugna, Martha; Mann, Shawna; Dube, Queen; Dreyer, Gavin; Hemmila, Ulla
Background: The epidemiology of acute kidney injury (AKI) in children in sub-Sahara Africa (SSA) is poorly described. The aim of this study was to establish the incidence, etiology, and outcomes of community-acquired AKI in pediatric admissions in Southern Malawi. Methods: We conducted a prospective observational study of pediatric admissions to a tertiary hospital in Blantyre between 5 February and 30 April 2016. Children were screened for kidney disease on admission with measurement of serum creatinine and assessment of urine output. The clinical presentation, etiology, and management of children with AKI were documented. Results: A total of 412 patients (median age 4 years, 52.6% male, and 7.5% human immunodeficiency virus [HIV] infected) were included in the study. Forty-five patients (10.9%) had AKI (Kidney Disease: Improving Global Outcomes [KDIGO] criteria), which was stage 3 in 16 (35.6%) patients. Sepsis and hypoperfusion, most commonly due to malaria ( n = 19; 42.2%), were the causes of AKI in 38 cases (84.4%). Three patients (6.7%) underwent peritoneal dialysis (PD) for AKI: 2 of them recovered kidney function, and the other one died. In-hospital mortality was 20.5% in AKI and 2.9% if no kidney disease was present ( p < 0.0001). Seventeen (47.2%) patients with kidney disease had persistent kidney injury on hospital discharge. Conclusion: Acute kidney injury occurs in 10.9% of pediatric admissions in Malawi and is primarily due to infections, particularly malaria. Acute kidney injury results in significantly increased in-hospital mortality. Urgent interventions are required to eliminate preventable causes of death in this region.